Design of Conveyor Scale Control and Monitoring Systems using HX711 Module Based On Arduino - Driyan Ramadhan, Alhadhi; Hartono, Hartono; Julaihah, Siti (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
The weighing and load control system on conveyor scales is a system that has a crucial role in ensuring the efficiency and safety of operations, especially in the aviation industry. In this context, this study aims to design and implement a control system and monitor the overload threshold on conveyor scales using the Arduino Uno-based HX711 module. The efficiency of using this tool can assist in the check-in process. Using this tool can help and speed up airport employees in the process of weighing baggage. This tool can process baggage weighing in less than 1 minute. In this study, using a scale equipped with a conveyor system. The design of the tool in this study for the maximum load that is set on the weighing system is 200 grams with a fine for every increase of 1 gram multiplied by IDR 1,000. If the weight of the load that is weighed exceeds the predetermined load limit, it will be integrated through the print out results that print from the weighing results. The print out contains the results of the weighing and fines that must be paid according to the excess weight. The results of testing the tool with a load weight of 117.7 grams did not experience an overload on the scales, while for a test with a load weight of 229.0 grams it experienced an overload of 29 grams with a fine of IDR 29,000